Conversion of peanut oil to hydrocarbons - Bascuñana, Ma. Victoria B. (College of Engineering, 1993)
Main raw material: Peanut oil -- Main product: Hydrocarbon mixture (petroleum ether) -- By-products: CaCl2, CaSO3, ZnCl2 -- Annual volume of production: 16,000,000 kgs -- Plant location: Aparri, Cagayan -- Total capital investment: P 309,907,000 -- Annual cost of production: P 948,891,000 -- Annual income: P 67,168,000 -- Rate of return on investment: 21.67% -- Payout time: 0.77 years